An iris puncture technique for restoration of the anterior chamber in vitrectomy for pediatric vitreoretinopathies - Chen, Chunli; Hu, Feng; Tian, Tian; Cheng, Yizhe; Fei, Ping; Zhao, Peiquan (Frontiers in Pediatrics, 2022)
Purpose: To present a novel usage of iris puncture assisted lensectomy with anterior vitrectomy or vitrectomy in pediatric patients with the absence of anterior chamber caused by various advanced vitreoretinopathies complicated with capsule-endothelial, iris-endothelial adhesion and secondary glaucoma. Design: Prospective study. Methods: Forty-one patients were enrolled in this consecutive, prospective study. The iris puncture was performed using 20G Vitrectomy Microsurgical Knife in all patients followed by the lensectomy with anterior vitrectomy or vitrectomy. Demographic information, the number of iris puncture time, surgical procedure, intraoperative and postoperative complications, therapy and prognosis were collected. Patients were followed up for at least 6 months. Results: Eighteen females and 23 males were included, with a mean age of 9.5 ± 7.5 months. The formation of anterior chamber formation was achieved in 28 (68.3%) eyes with only 1 initial episode of iris puncture, 11 (26.8%) patients required 2 episodes, and 3 episodes of iris puncture with an additional external drainage of subretinal fluid were needed in the remaining 2 (4.9%) patients. Except for iris incarceration, which occurred in 7 (17%) eyes during operation, there were no iridodialysis, subretinal fluid overflow during operation. At the last visit (mean: 12.16±5.38 months of follow-up), all eyes had a reconstructed anterior chamber with normal depth. No synechiae between the iris and the cornea occurred after surgery. The mean postoperative intraocular pressure was 6.23±1.64 mmHg. Cornea hazy vanished in 31 out of 41(75.6%) eyes, relieved in 8 out of 41 eyes (19.5%), 2 out of 41 eyes (4.88%) not changed. In the 25 eyes accepting vitrectomy and lensectomy, 20 out of 25 (80%) achieved different degrees of reattachment. Conclusions: The innovative iris puncture technique is an effective, simple and safe management for the anterior chamber disappearance caused by various advanced pediatric vitreoretinopathies, which helped to lower the intra ocular pressure and offer a chance for lensectomy with anterior vitrectomy or vitrectomy.